Academic Stress Coping of Padang City State Madrasah Aliyah Students - Ika Zulmai Fitra Yenti; Afrizal Sano (Universitas Negeri Padang, 2021)
This research is based on the existence of students who have not been able to perform behaviors or behaviors to remove, eliminate, and overcome stress in handling learning. This study aims to: (1) describe the handling of student academic stress in terms of handling emotional stress, and (2) describe the handling of academic stress in terms of handling academic stress in MAN Padang City. This type of research is descriptive research. The study population was 1,966 students with a sample of 301 students with Proportional Random Sampling. The instrument used was a questionnaire. The data analysis technique is the percentage. The results showed that: (1) handling of students 'academic stress in terms of handling academic stress was high, and (2) handling of students' academic stress in terms of handling focused problems was high.